Shoreline change analysis in the estuarine area of Rizhao based on remote sensing images and numerical simulation - Zhang, Zhaozi; Wang, Zhenlu; Liang, Bingchen; Leng, Xue; Yang, Bo; Shi, Luming (Frontiers in Marine Science, 2024)
The dynamic coastal environment is characterized by complex and variable interactions, often reflected in shoreline changes. This study analyzes shoreline changes in the estuarine area of Rizhao from 1985 to 2020 based on remote sensing images from Landsat 5 and Landsat 8. The largest shoreline changes were attributed to large-scale harbor construction, while relatively natural shorelines showed minor fluctuation. Due to the complex dynamics at the estuaries, shorelines on both sides of the estuaries were extracted and analyzed using the Digital Shoreline Analysis System (DSAS) in ArcGIS. Results indicate the southern shoreline experienced minor fluctuations, with a Linear Regression Rate (LRR) ranging from -2.27 m/y to 1.87 m/y. In contrast, the northern shoreline exhibited more significant fluctuations, with an LRR ranging from -7.62 m/y to 13.54 m/y, likely due to more intense dynamics near the cape and Muguan Island. Intra-annual seasonal shoreline was found to be more pronounced than inter-annual variations. Correlation analysis between the Net Shoreline Movement (NSM) and dynamic factor intensities across seasons revealed the highest correlation with runoff volume. Typhoon passages were observed to cause shoreline erosion, while sediment-laden runoff partially mitigated this erosion.